Cyberbullying and Child Protection in Cyberspace: Legal Perspectives and Practical Solutions - Prajaya, Fannzy Bayu Askar; Lubis, Muharman (LPPM STMIK Mardira Indonesia, 2025)
Cyberbullying has become a significant problem in the digital realm, particularly affecting children who are frequently susceptible to its detrimental consequences. This phenomenon presents significant hazards to the mental and physical health of victims, while also cultivating a perilous digital environment. This article aims to provide a comprehensive examination of cyberbullying from a legal perspective, analyzing its diverse impacts on individuals and society as a whole. It additionally examines efficacious ways for prevention and intervention. The research employs an interdisciplinary approach, drawing on insights from legislative frameworks, educational methods, and technological advancements to propose comprehensive solutions. The paper also analyzes real-life situations in Indonesia, including the incidents of